Acetaldehyde, Motivation and Stress: Behavioral Evidence of an Addictive ménage à trois - Brancato, Anna; Lavanco, Gianluca; Cavallaro, Angela; Plescia, Fulvio; Cannizzaro, Carla (Frontiers in Behavioral Neuroscience, 2017)
Acetaldehyde contributes to alcohol’s psychoactive effects through its own rewarding properties. Recent studies shed light on the behavioral correlates of acetaldehyde administration and the possible interactions with key neurotransmitters for motivation, reward and stress-related response, such as dopamine and endocannabinoids. This mini review critically examines acetaldehyde psychoactive properties, focusing on behavioral investigations able to unveil acetaldehyde motivational effects and their pharmacological modulation in vivo. Similarly to alcohol, rats spontaneously drink acetaldehyde, whose presence is detected in the brain following chronic self-administration paradigm. Acetaldehyde motivational properties are demonstrated by operant paradigms tailored to model several drug-related behaviors, such as induction and maintenance of operant self-administration, extinction, relapse and punishment resistance. Acetaldehyde-related addictive-like behaviors are sensitive to pharmacological manipulations of dopamine and endocannabinoid signaling. Interestingly, the acetaldehyde-dopamine-endocannabinoids relationship also contributes to neuroplastic alterations of the NPYergic system, a stress-related peptide critically involved in alcohol abuse. The understanding of the ménage-a-trois among acetaldehyde, reward- and stress-related circuits holds promising potential for the development of novel pharmacological approaches aimed at reducing alcohol abuse.